Day 3 Wed, March 28, 2018 2018
DOI: 10.2118/190382-ms
|View full text |Cite
|
Sign up to set email alerts
|

Results of Alkaline-Surfactant-Polymer Flooding Pilot at West Salym Field

Abstract: The West Salym oil field is located in the West Siberian oil province (Russia). Its reservoir conditions are typical for the region: sandstone formation with temperatures as high as 83 °C, low crude oil viscosities of about 2 cP, and brine salinities in the range of 14,000-16,000 ppm. The field is waterflooded to maintain the reservoir pressure close to its initial level and to optimize oil recovery. Oil production from West Salym peaked in 2011 and since declined with increasing water cuts. The expected ultim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Among those techniques is the temperature log, which could be utilized to avoid the risk of injecting out of the zone. Saturation logs are also useful for monitoring the vertical saturation distribution and propagation of the oil bank …”
Section: Field Monitoring Of Surfactant Floodingmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those techniques is the temperature log, which could be utilized to avoid the risk of injecting out of the zone. Saturation logs are also useful for monitoring the vertical saturation distribution and propagation of the oil bank …”
Section: Field Monitoring Of Surfactant Floodingmentioning
confidence: 99%
“…Saturation logs are also useful for monitoring the vertical saturation distribution and propagation of the oil bank. 201…”
Section: Field Monitoring Of Surfactant Floodingmentioning
confidence: 99%
“…The positive effects of alkali on polymer solution viscosity development, adsorption, and injectivity, and the long-term stability of polymers in alkali solutions were explored by Nurmi et al [ 16 ], indicating additional economic benefits of AP flooding over polymer flooding. While various chemical enhanced oil recovery (EOR) projects have been successfully field-tested and implemented for light oils (e.g., Guo et al [ 17 ], Pandey et al [ 18 ], and Volokitin et al [ 19 ]), heavy oils require additional chemicals to polymers for increased production over waterflooding. Alkali and surfactant injection induces emulsion formation and channel blockage in waterflooded cores and micromodels (e.g., Bryan et al [ 20 ], Dong et al [ 21 ], Xie et al [ 22 ], and Xiao et al [ 23 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [21] also indicated that even in cases of low TAN, a synergistic effect between the injected synthetic surfactants and the in situ surfactants leads to an ultra-low interfacial tension [22]. Additionally, injecting alkali into reservoirs with low TAN is beneficial as alkali helps reduce surfactant adsorption [23]. The adsorption reduction happens because of the increasing pH level of the system.…”
Section: Introductionmentioning
confidence: 99%
“…A higher pH increases the negative charge of the reservoir rock and surfactant molecules, so more electrical repulsion between surfactant molecule and reservoir rock occurs [24,25]. Since alkali is less costly than surfactant, using it even with low TAN crude oil can be economically beneficial as it can significantly lower the surfactant consumption [5,23].…”
Section: Introductionmentioning
confidence: 99%